Ultrasound-Assisted Extraction and Characterization of Polyphenols from Apple Pomace, Functional Ingredients for Beef Burger Fortification - Luna Pollini; Francesca Blasi; Federica Ianni; Luca Grispoldi; Simone Moretti; Alessandra Di Veroli; Lina Cossignani; Beniamino Terzo Cenci-Goga (Molecules, 2022)
Currently, there is an increasing interest to valorise agri-food waste containing bioactive compounds with potential health benefits. In this paper, the recovery of functional molecules from apple pomace, the most abundant by-product of the apple processing industry, was carried out by ultrasound-assisted extraction (UAE) on fresh and freeze-dried samples. UAE extract, obtained by double extraction of freeze-dried apple pomace, was subjected to chromatographic and spectrophotometric characterization. It showed good levels of total phenol content, high antioxidant activity, and interesting antioxidant compounds (quercetin derivatives, chlorogenic acid, phloridzin). Subsequently, freeze-dried apple pomace, containing 40.19% of dietary fibre, was used as a fortifying agent for beef burgers (4% and 8%). The results concerning colour and sensory analysis of the fortified products were graded even better than the control (0%). The improved fibre and phenol content, together with the neutral flavour, represent the most interesting characteristics of fortified burgers. The results confirm that UAE was a successful technique for extracting phenol compounds and that the addition of apple pomace represents a valid approach to increase the health properties and palatability of beef burgers, including for consumers who do not like meat.